The study of diagnostic accuracy of fine needle aspiration cytology of salivary glands lesions in Hospital Sultanah Bahiyah - Noh, Khairul Bariah (2018)
Introduction: Salivary glands lesions comprise about 2 to 6.5% of all head and neck neoplasms in adult. The common presentation is an enlarged mass which usually accessible for fine needle aspiration cytology. Enlargement or masses of the salivary gland have a wide differential diagnosis, as they can result from inflammatory responses, infectious lesions, or neoplasms. Objective: To determine the accuracy of Fine Needle Aspiration Cytology (FNAC) as a preoperative assessment of salivary glands lesions in Hospital Sultanah Bahiyah (HSB) a tertiary hospital. Methods: All patients who had undergone salivary glands surgery from January 2009 to December 2016 were included. The diagnostic value of FNAC in comparison with histopathology was calculated for benign and malignant neoplasms based on sensitivity, specificity, positive predictive value and negative predictive value. The definitive histopathological diagnosis was compared with the preoperative FNAC diagnosis. Results: There were a total number of 138 patients in HSB who had a pre-operative FNAC result and underwent salivary glands lesion surgery from 2009 to 2016. Total of 131 patients were included in this study. Seven patients were excluded in view FNAC was done at other centre. The overall FNAC accuracy in the diagnosis of salivary glands lesion was 72.5 per cent. Conclusions: FNAC is a useful procedure as the diagnostic screening tool of salivary gland lesion as it can aid surgeon in patient’s management.